THE CORRELATION BETWEEN VERBAL-LINGUISTIC APTITUDE AND INVESTIGATIVE INTEREST AMONG ADOLESCENTS WITH AUTISTIC SPECTRUM DISORDER AT SPECIAL EDUCATION SCHOOLS IN SOLO RAYA - Atalya Dheaputri Wibowo; Erma Kumala Sari; Tias Martika (Journal of Disability, 2025)
This research was conducted to discover the correlation between verbal-linguistic aptitude and investigative interest among adolescents with Autistic Spectrum Disorder (ASD) at Special Education Schools in Solo Raya. The total sample consisted of 16 adolescents with ASD in the age group of 10 - 21 years. The sampling technique conducted for this research is purposive sampling. To meet the objective of the research, multiple intelligences aptitude and the vocational interest psychological scale by Yuliastuti (2022) were used. The data was analyzed by using descriptive analysis and a Kendall’s Tau statistical correlation type in SPSS 25. This research reveals a correlation coefficient of 0.310 with p = 0.124 (p > 0.05), indicating that there is no correlation between verbal-linguistic aptitude and investigative interest among adolescents with ASD in Special Education Schools in Solo Raya.